Bio-based mould pressing material

By activating lignin and introducing cyclic acetal structure, lignin and cellulose are recombined, and the problems of complex preparation process and insufficient molding properties of bio-based materials are solved, and efficient and low-cost preparation of bio-based molding materials is achieved, suitable for scale .

CN119192686APending Publication Date: 2024-12-27FUJIAN AGRI & FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411322386.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The preparation process of existing biomass is complex, the conversion cost is high, and the lignin cannot be directly used, which makes it difficult to achieve high value and large-scale utilization of wood biomass. At the same time, the molding properties of existing biomass materials are insufficient and cannot replace petroleum. Base material.

Method used

By activating lignin and cellulose, recombination of lignin and cellulose, introducing a cyclic acetal structure, using the curing crosslinking characteristics of lignin to achieve bonding and cellulose crosslinking, and a bio-based molding with high molding properties and strength was prepared. Material.

Benefits of technology

It realizes the high-value utilization of wood biomass, reduces the production temperature and pressure of molded products, improves the strength and water resistance of the material, simplifies the preparation process, is suitable for large-scale and industrial production, and replaces petroleum-based polymer materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192686A_ABST
    Figure CN119192686A_ABST
Patent Text Reader

Abstract

The invention discloses a bio-based mould pressing material, and belongs to the technical field of chemical engineering. The main components of the bio-based mold pressing material are lignin and cellulose which are uniformly mixed, the side chain of a phenol unit of the lignin contains a cyclic acetal structure of 1, 3-dioxane, and the integral of alpha hydrogen atoms in the cyclic acetal structure is 2% greater than that of hydrogen atoms in methoxyl. Lignin and cellulose in the wood biomass are recombined and activated, a cyclic acetal structure is introduced to the lignin, and the lignin and the cellulose are crosslinked and densified through hot pressing by utilizing the properties of melting, flowing and self-crosslinking of the lignin at high temperature, so that various molded products are obtained; the prepreg can effectively replace traditional thermoplastic and thermosetting mold pressing prepregs, and has important significance for reducing use of petroleum-based plastics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical engineering, and in particular relates to a bio-based molding material. Background Art

[0002] Bio-based materials are made by biological, chemical and physical means, including the contents and residues of crop straw, trees and other plants and animals. One of the main ways to prepare bio-based polymer materials is to prepare polymer monomers by fermenting glucose and then converting polymer monomers into polymers (such as plastics) by polymerization. This process requires the extraction of cellulose and starch from biomass, and then breaking them down into small molecules (such as lactic acid, succinic acid, propylene glycol), and then polymerizing these small molecules into macromolecules. However, the above-mentioned conversion process has a complex production process and high conversion cost, especially the lignin present in woody biomass cannot be directly utilized. On the other hand, the products obtained by pressing artificial boards using biomass materials are not moldable, and they are still wood boards in essence. Therefore, the development of a simple and easy-to-make bio-based molding material that can be directly used for molding and preparing various types of products is of great significance for promoting the use of bio-based materials and reducing the use of petroleum-based materials and non-degradable plastics. Summary of the invention

[0003] In order to solve the problems existing in the high-value and large-scale utilization of woody biomass, the present invention provides a bio-based molding material. The present invention activates woody biomass to reorganize lignin and cellulose in the woody biomass, activates lignin, introduces a cyclic acetal structure thereon, and utilizes the property that the cyclic acetal structure of lignin opens at high temperature to induce lignin curing and cross-linking, thereby achieving lignin bonding cellulose recombination, and then cross-linking and curing of lignin and cellulose to obtain a molded product.

[0004] To achieve the above object, the present invention adopts the following technical solution: A bio-based molding material, the main components of which are uniformly mixed lignin and cellulose, the phenol unit side chain of the lignin contains a 1,3-dioxane cyclic acetal structure, and the chemical shifts of the alpha carbon atom and the hydrogen atom of the cyclic acetal structure in a two-dimensional nuclear magnetic resonance spectrum (HSQC) are respectively TM H: 4.5-5.5 ppm, TMC: 92-105 ppm, and the integral of alpha hydrogen atoms in the cyclic acetal structure should be greater than 2% of the integral of hydrogen atoms in methoxy groups. Due to the influence of the methoxy content and the β-O-4 unit content in the lignin unit, the maximum value of the integral ratio of alpha hydrogen atoms in the cyclic acetal structure to the integral ratio of hydrogen atoms in methoxy groups is about 15%, so the upper limit is not limited in the claims of the present invention, because this is well known to those skilled in the art and is limited by the natural material itself.

[0005] The present invention does not require that all phenol unit side chains in the lignin are converted into cyclic acetal structures, but more cyclic acetal structures will make the activity of lignin higher and more likely to undergo curing and crosslinking reactions during hot pressing. This feature has a positive effect on reducing the temperature and pressure required during molding and enhancing the strength of molded products. In the present invention, since the lignin methoxy group is relatively stable, the ratio of the lignin unit with cyclic acetal structure to the hydrogen atom integration in the methoxy group can be used to reflect the ratio of the lignin unit with cyclic acetal structure to the whole lignin unit. The present invention finds that when the alpha hydrogen atom integration in the cyclic acetal structure is greater than 2% of the hydrogen atom integration in the methoxy group, the ratio of the lignin unit with cyclic acetal structure to the whole lignin unit is about greater than 10%, so that the lignin has better activity. The cyclic acetal structure can be obtained by reacting lignin biomass or lignin with aldehyde.

[0006] Furthermore, taking the total mass percentage as 100%, the mass percentage of cellulose in the bio-based molding material is 50-70%, the mass percentage of lignin is 30-50%, and hemicellulose and its derivatives (such as xylose, furfural, etc.) and very small amounts of other impurities may be included therein in small amounts if they are not completely removed.

[0007] Furthermore, the particle size of the molding material is preferably 10-100 meshes, so that the components are more easily mixed evenly. In order to ensure good material fluidity and denser fibers during molding, the particle size of the prepared molding material should be smaller than a certain size. However, as the size decreases, the energy consumption of particle crushing will increase, and the fibers will become shorter, resulting in a decrease in the strength of the resulting molded product.

[0008] In industry, the molding material can be prepared by direct reaction of woody biomass containing lignin and cellulose as raw materials, and its preparation includes the following steps: 1) mixing woody biomass with a first solvent, a second solvent, and a catalyst to react to obtain a mixed solution containing cellulose solids; 2) adding water to the mixed solution obtained in step 1) to precipitate lignin, thereby obtaining a mixed solution containing cellulose solids and lignin solids; 3) performing solid-liquid separation on the mixed solution obtained in step 2) to obtain a solid component and a solution component containing cellulose and lignin; 4) Drying the solid component obtained in step 3) to obtain the bio-based molding material.

[0009] The molding material can also be obtained by pre-preparing lignin containing the cyclic acetal structure of 1,3-dioxane, and then compounding it with a cellulose-containing biomass material (which may or may not contain lignin that has not been activated). The preparation method of the lignin containing the cyclic acetal structure of 1,3-dioxane is to mix the wood biomass with the first solvent, the second solvent, and the catalyst to react to obtain a mixed solution containing cellulose solids, remove the cellulose solids through solid-liquid separation, and then add water to the obtained reaction solution to precipitate the lignin solids.

[0010] In the preparation, the woody biomass used is raw materials such as straw, wood, bamboo, etc. containing lignin, cellulose and hemicellulose, and its main physical form is flake, granular or powder.

[0011] During the preparation, the first solvent is one or more of 1,4-dioxane, 1,3-dioxane, tetrahydrofuran, 2-methyltetrahydrofuran, γ-valerolactone, and acetic acid. The purpose of using the first solvent is to effectively separate lignin and cellulose, dissolve lignin, soften the cell wall of wood biomass, and make the prepared molding material have better compressibility, so as to improve the density of the molded product, thereby improving its crosslinking density and water resistance.

[0012] During the preparation, the second solvent is an aqueous solution of one or more of formaldehyde, acetaldehyde, propionaldehyde, and butyraldehyde with a mass concentration of 35%-50%. The purpose of using the second solvent is to use the aldehydes in the second solvent to form a 1,3-dioxane structure with the lignin side chain after the first solvent dissolves the lignin, so as to inhibit the condensation of lignin into macromolecules and improve the activity and fluidity of the formed cyclic acetal lignin.

[0013] During the preparation, the catalyst is sulfuric acid or hydrochloric acid. The purpose of using the catalyst is to partially hydrolyze lignin and catalyze the reaction of aldehydes with lignin. The hydrolysis of lignin is conducive to the dissolution of lignin and the acetalization reaction with the aldehyde in the second solvent; in addition, the hydrolysis of lignin helps to reduce its molecular weight and softening temperature. In addition, the acid can also hydrolyze hemicellulose into monosaccharides or oligosaccharides or other derivatives soluble in the solvent, so that they can be separated from cellulose and lignin by solid-liquid separation.

[0014] During the preparation, the amount of wood biomass used is 3-30% of the total mass of the first solvent and the second solvent; the amount of the first solvent used accounts for 60%-99.4% of the total mass of the first solvent and the second solvent; the amount of the catalyst used (measured in absolute mass excluding water) is 0.1-5% of the total mass of the first solvent and the second solvent.

[0015] In the preparation, the temperature of the reaction of the woody biomass with the first solvent, the second solvent and the catalyst is 70-140°C and the time is 20min-8h. When a lower temperature is used, a longer reaction time is preferred. For example, when the preferred temperature is 130-140°C, the suitable reaction time is 20min-1h; when the preferred temperature is 100-120°C, the suitable reaction time is 1-3h; when the preferred temperature is 80-100°C, the suitable reaction time is 3-8h.

[0016] During the preparation, the amount of water added is 2-10 times the total volume of the first solvent and the second solvent used. The purpose of adding water is to change the polarity of the solution, so that the lignin dissolved in the organic solvent is precipitated and deposited on the cellulose surface; at the same time, the monosaccharides or oligosaccharides or other derivatives derived from hemicellulose are still retained in the solution, and then the solid phase components (cellulose and lignin) and the liquid phase components (hemicellulose derivatives and other components) are separated by solid-liquid separation.

[0017] Furthermore, during the preparation, the pH of the mixed solution can be adjusted to 6-7 with alkali, and then water can be added to mix. Alternatively, after solid-liquid separation, the solid component can be washed with clean water to a pH of 6-7.

[0018] In step 4), the obtained molding material is dried to a moisture content of less than 5%. A certain moisture content can reduce the softening temperature of lignin, reduce the hot pressing temperature or shorten the hot pressing time, but if the moisture content is too high, the steam generated during hot pressing is likely to cause the molded product to bulge and crack, and also increase the energy consumption of evaporating water. The present invention has found that drying to a moisture content of less than 5% has a better comprehensive effect.

[0019] The organic solvent activation treatment method of the present invention is relatively mild, and can remove most of the hemicellulose, pectin, protein and other components in the wood biomass, retain the lignin and cellulose components, and then through the steps of water separation, filtration, washing, drying and the like, the activated wood biomass can be prepared into a molding material. When the wood biomass is activated, the cell wall is deconstructed and softened, and the fluidity of the lignin is increased; the removal of components such as hemicellulose increases the relative proportion of lignin; the obtained molding material can utilize the melting, flow and self-crosslinking properties of lignin at high temperature, and crosslink and densify through hot pressing, and finally obtain a molded product.

[0020] The bio-based molding material can be directly molded, and the molding temperature is 160-250°C, the pressure is 2-40MPa, and the pressing time is 10s-60min. The higher the hot pressing temperature used, the shorter the hot pressing time. For example, when the preferred temperature is 180-200°C, the hot pressing time is 5-15 min; when the preferred temperature is 200-220°C, the hot pressing time is 2-5min; when the preferred temperature is 220-240°C, the hot pressing time is 10 s-2 min. In practical applications, the hot pressing conditions can be adjusted according to actual needs (such as thickness, density, water resistance, strength, etc.).

[0021] When molding the obtained molding material, appropriate acid, such as sulfuric acid, hydrochloric acid, and phosphoric acid, can be added to accelerate the curing speed of the material and reduce the molding conditions (such as reducing the molding time, reducing the molding pressure, and reducing the molding temperature); pigments and dyes can be added to obtain moldings of different colors; flame retardants can be added to improve the flame retardant properties of the molded products; and waterproofing agents can also be added to further improve the waterproof properties of the molded products.

[0022] Specifically, the idea of ​​the present invention is to remove hemicellulose and other components (such as ash, protein, pectin, etc.) in woody biomass as much as possible, and mainly retain cellulose and lignin components; at the same time, lignin is activated and modified by molecules such as formaldehyde, acetaldehyde and propionaldehyde to obtain active lignin. Taking advantage of the characteristics of active lignin that it is easy to soften, flow and cross-link during hot pressing, cellulose is bonded to form a fiber-reinforced lignin composite material. The above process can be prepared by directly reacting the woody biomass material containing lignin and cellulose through activation treatment, or it can be prepared and separated to obtain active lignin, and then compounded with other cellulose-containing biomass materials (such as wood particles, wood chips, wood fibers) to obtain molding materials.

[0023] Since lignin has high activity after the introduction of cyclic acetal structure, the obtained bio-based molding material can be molded at a lower temperature (160-250℃) or a lower pressure (2-40 MPa) to prepare boards or other special-shaped structural products. The so-called molding, that is, the usual sense of molding (also known as molding, pressing or compression molding), is a method of putting powdered, granular or fibrous materials into the mold cavity at the molding temperature, and then closing the mold and pressurizing it to form and solidify it.

[0024] This method greatly improves the feasibility of high-value utilization of wood biomass and facilitates the large-scale and industrial application of wood biomass. At the same time, the molded material can replace petroleum-based polymers and their composite materials, especially for the preparation of various daily necessities that are friendly to human health and the environment.

[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention creatively utilizes the softening, flowability and self-crosslinking properties of activated cyclic acetal lignin at relatively low temperatures, thereby making the activated wood biomass moldable.

[0026] (2) The present invention also provides a method for directly manufacturing the molding material of the present invention from woody biomass materials. The activation treatment temperature used in the method is relatively mild. At the same time, the use of two solvents can effectively retain the activity of lignin and prevent the lignin from undergoing condensation cross-linking reaction in advance during the extraction process. That is, through the acetalization reaction of aldehydes and lignin, the cross-linking reaction of lignin in advance during the separation process is inhibited to obtain cyclic acetal lignin with a smaller molecular weight and higher activity. This idea allows the cyclic acetal lignin to soften and flow better during hot pressing, and undergo self-crosslinking and curing to form a molded product with higher strength and water resistance.

[0027] (3) Compared with the composite materials prepared by conventional methods using polylactic acid, unsaturated polyester, epoxy resin, polyvinyl chloride, etc. as the resin matrix, the molding material prepared by the present invention does not need to add other petroleum-based resin matrix. At the same time, the present invention has simple operation steps and mild pretreatment conditions, and directly converts biomass into molding materials, avoiding the cumbersome process of converting cellulose into bio-based plastics in traditional biomass chemical industry, making the present invention easy to achieve large-scale and industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The structural formula of the lignin with a cyclic acetal structure of the present invention and its corresponding nuclear magnetic resonance spectrum are shown. DETAILED DESCRIPTION

[0029] The present invention finds that lignin biomass is activated to reorganize lignin and cellulose therein, activate lignin, and introduce a cyclic acetal structure thereon, so that part or all of the lignin is converted into a cyclic acetal lignin with a cyclic acetal structure, and the cyclic acetal structure of lignin is opened at high temperature to initiate the curing and cross-linking of lignin, so as to achieve the reorganization of lignin bonding cellulose to obtain a molded product. The lignin has a high activity after the introduction of the cyclic acetal structure, and can be molded to prepare a plate or other special-shaped structure product at a lower temperature or lower pressure, making it more suitable for industrial application, thereby obtaining a fully lignin-based molded material. This molded material can be obtained by directly reacting woody biomass, or by activating lignin (for example, by separating lignin solids separately in steps 1 and 2 of the preparation method of the present invention) and then compounding with other biomass materials to obtain it.

[0030] In most cases, the cellulose content of natural wood biomass is 35-45%, the lignin content is 10-30%, and the hemicellulose content is 10-35%. Due to the lack of sufficient lignin to bond cellulose, the performance of the molded material directly prepared from untreated wood biomass is poor. Through the activation treatment of the present invention, most or all of the hemicellulose is removed, and the mass content of cellulose in the prepared molded material can be increased to 50-70%, and the mass content of lignin can be increased to 30-50%, so that the molded material contains a sufficient proportion of lignin for curing and cross-linking reaction.

[0031] The content of cellulose and lignin in the molded material can be analyzed by the NREL method of the National Renewable Energy Laboratory of the United States. The specific steps are to crush the molded material through an 80-mesh sieve, weigh 0.3 grams of the sieved molded material in 3 ml of 72% concentrated sulfuric acid, stir and react at 25 degrees Celsius for 1 hour, then add 84 ml of water to dilute the sulfuric acid to a concentration of 4%, add the solution to a closed container and react at 120 degrees Celsius for 1 hour. After the reaction is completed, the solid is separated to obtain acid-insoluble lignin. The glucose content in the solution is determined by liquid chromatography, and the acid-soluble lignin content in the solution is determined by ultraviolet spectrophotometer, then: , .

[0032] The ratio of cyclic acetal structure of lignin in the molded material can be analyzed by the following steps. 1 gram of the molded material is added to 10 ml of dioxane, stirred at 30 degrees Celsius for 1 hour, the solution is separated by filtration, and the dioxane in the solution is evaporated at 60 degrees Celsius to obtain lignin. 200 mg of lignin is dissolved in 1 ml of DMSO-d6, and its HSQC nuclear magnetic spectrum is measured by nuclear magnetic resonance spectrometer. Figure 1 The cyclic acetal structure of the lignin side chain is shown in the HSQC NMR spectrum. TM H: 4.5-5.5ppm, TM C: There is an obvious characteristic signal at 92-105 ppm.

[0033] HSQC NMR spectra TM H: 4.5-5.5 ppm; TM C: 92-105 ppm is integrated to obtain the alpha hydrogen atom integral in the cyclic acetal structure, and the HSQC NMR spectrum is TM H: 3.3-4.2 ppm; TMC: 54-58 ppm is integrated to obtain the integral of methoxy hydrogen atoms in the methoxy structure. From this, the ratio of alpha hydrogen atoms in the cyclic acetal structure to hydrogen atoms in the methoxy group can be calculated, and then the ratio of lignin units with cyclic acetal structures to the entire lignin units can be determined, so that the molding material has better performance.

[0034] In order to better evaluate the performance of the molded material, in the embodiment, the molded material is placed in a mold and hot-pressed into a molded sheet product, and then the static bending strength and water resistance of the molded sheet product are tested respectively in accordance with GB / T 17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels".

[0035] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0036] Example 1 100 g of eucalyptus wood powder (particle size greater than 10 mesh), 900 g of 1,4-dioxane, 100 g of formaldehyde solution (35 wt.%), and 50 g of concentrated hydrochloric acid (concentration 37%) were added to a 2-liter reactor, stirred and heated to 80 ° C, and reacted for 5 h. After the reaction, the reaction solution was adjusted to pH 6-7 with sodium hydroxide, and then poured into 10 liters of water to precipitate lignin. The mixed solution was filtered to obtain a solid residue; the solid residue was dried at 105 ° C to a moisture content of less than 5%, and a moldable granular material with a dry weight of about 64 g was obtained, which was composed of 62% cellulose, 35% lignin, and 3% other components. The integral of alpha hydrogen atoms in the cyclic acetal structure is 9.5% of the integral of hydrogen atoms in the methoxy group.

[0037] 48 grams of the obtained moldable granules were evenly spread in a square mold of 100 mm×100 mm×25 mm, and then hot pressed at 240°C and 16 MPa for 1 min. After the hot pressing, cooling water was introduced, and the mold temperature was lowered to below 60°C. After the pressure was released, the mold was taken out to obtain the final molded product.

[0038] According to GB / T 17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels", the static bending strength and water resistance of the molded products were tested. The results showed that its density was 1.12 g / cm 3 The static bending strength is 37 MPa and the thickness expansion rate of water absorption after 24 hours is 7%.

[0039] Example 2 Except that 100 g of eucalyptus wood powder used in Example 1 was replaced by 100 g of F5H-poplar wood powder (with a particle size greater than 10 mesh), the other steps were the same as in Example 1, and the dry weight of the moldable granules was about 67 g, and the composition thereof was 60% cellulose, 38% lignin, and 2% other components. The integral of alpha hydrogen atoms in the cyclic acetal structure was 15% of the integral of hydrogen atoms in the methoxy group.

[0040] 48 grams of the obtained moldable granules were evenly spread in a square mold of 100 mm×100 mm×25 mm, and then hot pressed at 240°C and 16 MPa for 1 min. After the hot pressing, cooling water was introduced, and the mold temperature was lowered to below 60°C. After the pressure was released, the mold was taken out to obtain the final molded product.

[0041] According to GB / T 17657-2013 "Test methods for physical and chemical properties of artificial boards and veneer artificial boards", the static bending strength and water resistance of the molded products were tested respectively. The results showed that its density was 1.21 g / cm 3 The static bending strength is 42 MPa, and the thickness expansion rate of water absorption after 24 hours is 3%.

[0042] Example 3 Except that the amount of formaldehyde solution (35 wt.%) added in Example 1 was reduced from 100 g to 5 g, the other steps were the same as in Example 1, and the dry weight of the moldable granules was about 60 g, and the composition thereof was 64% cellulose, 32% lignin, and 4% other components. The integral of alpha hydrogen atoms in the cyclic acetal structure was 2% of the integral of hydrogen atoms in the methoxy group.

[0043] 48 grams of the obtained moldable granules were evenly spread in a square mold of 100 mm×100 mm×25 mm, and then hot pressed at 240°C and 16 MPa for 1 min. After the hot pressing, cooling water was introduced, and the mold temperature was lowered to below 60°C. After the pressure was released, the mold was taken out to obtain the final molded product.

[0044] According to GB / T 17657-2013 "Test methods for physical and chemical properties of artificial boards and veneer artificial boards", the static bending strength and water resistance of the molded products were tested respectively. The results showed that its density was 1.04 g / cm 3 The static bending strength is 16 MPa, and the thickness expansion rate after 24 h water absorption is 14%.

[0045] Example 4 Except that the mass of the eucalyptus wood powder used in Example 1 was reduced from 100 g to 30 g, the other steps were the same as in Example 1, and the dry weight of the moldable granules was about 20 g, and the composition thereof was 64% cellulose, 33% lignin, and 3% other components. The integral of alpha hydrogen atoms in the cyclic acetal structure was 9.8% of the integral of hydrogen atoms in the methoxy group.

[0046] 48 grams of the obtained moldable granules were evenly spread in a square mold of 100 mm×100 mm×25 mm, and then hot pressed at 240°C and 16 MPa for 1 min. After the hot pressing, cooling water was introduced, and the mold temperature was lowered to below 60°C. After the pressure was released, the mold was taken out to obtain the final molded product.

[0047] According to GB / T 17657-2013 "Test methods for physical and chemical properties of artificial boards and veneer artificial boards", the static bending strength and water resistance of the molded products were tested respectively. The results showed that its density was 1.14 g / cm 3 The static bending strength is 38 MPa and the thickness expansion rate of water absorption after 24 hours is 6%.

[0048] Example 5 300 g of bamboo powder (particle size greater than 50 mesh), 800 g of γ-valerolactone, 200 g of acetaldehyde solution (40 wt.%), and 2 g of concentrated hydrochloric acid (concentration 37%) were added to a 2-liter reactor, stirred and heated to 140 °C, and reacted for 20 minutes. After the reaction, the reaction solution was poured into 20 liters of water to precipitate lignin. The mixed solution was filtered to obtain a solid residue, which was washed to a pH of 6-7; the solid residue was dried at 105 °C to a moisture content of less than 5%, and a moldable granular material with a dry weight of about 181 g was obtained, which was composed of 56% cellulose, 37% lignin, and 7% other components. The integral of alpha hydrogen atoms in the cyclic acetal structure is 4.9% of the integral of hydrogen atoms in the methoxyl group.

[0049] 48 grams of the obtained moldable granules were evenly spread in a square mold of 100 mm×100 mm×25 mm, and then hot pressed at 300°C and 30 MPa for 20 s. After the hot pressing, cooling water was introduced, and the mold temperature was lowered to below 60°C, and the mold was taken out after the pressure was released to obtain the final molded product.

[0050] According to GB / T 17657-2013 "Test methods for physical and chemical properties of artificial boards and veneer artificial boards", the static bending strength and water resistance of the molded products were tested respectively. The results showed that its density was 1.39 g / cm 3 The static bending strength is 15 MPa and the thickness expansion rate of water absorption after 24 hours is 6%.

[0051] Example 6 100 g corn stalk powder (particle size greater than 100 mesh), 950 g tetrahydrofuran, 500 g propionaldehyde (50 wt.%), and 50 g concentrated hydrochloric acid (concentration 37%) were added to a 2-liter reactor, stirred and heated to 70 °C, and reacted for 8 h. After the reaction, the reaction solution was adjusted to pH 6-7 with sodium hydroxide, and then poured into 2 liters of water to precipitate lignin. The mixed solution was filtered to obtain a solid residue; the solid residue was dried at 105 °C until the moisture content was less than 5%, and a moldable granular material with a dry weight of about 55 g was obtained, which was composed of 65% cellulose, 30% lignin, and 5% other components. The integral of alpha hydrogen atoms in the cyclic acetal structure is 6.8% of the integral of hydrogen atoms in the methoxy group.

[0052] 48 grams of the obtained moldable granules were evenly spread in a square mold of 100 mm×100 mm×25 mm, and then hot pressed at 180°C and 16 MPa for 10 min. After the hot pressing, cooling water was introduced, and the mold temperature was lowered to below 60°C. After the pressure was released, the mold was taken out to obtain the final molded product.

[0053] According to GB / T 17657-2013 "Test methods for physical and chemical properties of artificial boards and veneer artificial boards", the static bending strength and water resistance of the molded products were tested respectively. The results showed that its density was 1.38g / cm 3 The static bending strength is 49 MPa and the thickness expansion rate of water absorption after 24 hours is 1%.

[0054] Example 7 100 g corn stalk powder (particle size greater than 100 mesh), 900 g 1,4-dioxane, 100 g formaldehyde solution (35 wt.%), and 1 g concentrated sulfuric acid (98%) were added to a 2-liter reactor, stirred and heated to 140 °C, and reacted for 1 h. After the reaction, the reaction solution was adjusted to pH 6-7 with sodium hydroxide, and then poured into 10 liters of water to precipitate lignin. The mixed solution was filtered to obtain a solid residue; the solid residue was dried at 105 °C until the moisture content was less than 5%, and a moldable granular material with a dry weight of about 57 g was obtained, which was composed of 61% cellulose, 32% lignin, and 7% other components. The integral of alpha hydrogen atoms in the cyclic acetal structure is 6.2% of the integral of hydrogen atoms in the methoxyl group.

[0055] 48 grams of the obtained moldable granules were evenly spread in a square mold of 100 mm×100 mm×25 mm, and then hot pressed at 180°C and 8 MPa for 10 min. After the hot pressing, cooling water was introduced, and the mold temperature was lowered to below 60°C, and the mold was taken out after the pressure was released to obtain the final molded product.

[0056] According to GB / T 17657-2013 "Test methods for physical and chemical properties of artificial boards and veneer artificial boards", the static bending strength and water resistance of the molded products were tested respectively. The results showed that its density was 1.07 g / cm 3 The static bending strength is 34 MPa, and the thickness expansion rate of water absorption after 24 hours is 8%.

[0057] Example 8 100 g of spruce wood powder (particle size greater than 40 mesh), 600 g of acetic acid and 400 g of acetaldehyde solution (40 wt.%), and 30 g of concentrated sulfuric acid (concentration 98%) were added to a 2-liter reactor, stirred and heated to 100 °C, and reacted for 2 h. After the reaction, the reaction solution was poured into 15 liters of water to precipitate lignin. The mixed solution was filtered to obtain a solid residue, and the solid residue was washed to a pH of 6-7; the solid residue was dried at 105 °C to a moisture content of less than 5%, and a moldable granular material with a dry weight of about 72 g was obtained, which was composed of 50% cellulose, 45% lignin, and 5% other components. The integral of alpha hydrogen atoms in the cyclic acetal structure is 3.1% of the integral of hydrogen atoms in the methoxy group.

[0058] 48 grams of the obtained moldable granules were evenly spread in a square mold of 100 mm×100 mm×25 mm, and then hot pressed at 140°C and 16 MPa for 10 min. After the hot pressing, cooling water was introduced, and the mold temperature was lowered to below 60°C. After the pressure was released, the mold was taken out to obtain the final molded product.

[0059] According to GB / T 17657-2013 "Test methods for physical and chemical properties of artificial boards and veneer artificial boards", the static bending strength and water resistance of the molded products were tested respectively. The results showed that its density was 1.08 g / cm 3 The static bending strength is 17 MPa, and the thickness expansion rate of water absorption after 24 hours is 20%.

[0060] Example 9 100 g of paulownia wood powder (particle size greater than 200 mesh), 800 g of 1,4-dioxane, 200 g of formaldehyde solution (40 wt.%), and 20 g of concentrated sulfuric acid (98%) were added to a 2-liter reactor, stirred and heated to 120°C, and reacted for 1 h. After the reaction, the reaction mixture was poured into 6 liters of water to precipitate lignin. The mixture was filtered to obtain a solid residue, and the solid residue was washed to a pH of 6-7; the solid residue was dried at 105°C to a moisture content of less than 5%, and a moldable granular material with a dry weight of about 58 g was obtained, which was composed of 57% cellulose, 40% lignin, and 3% other components. The integral of alpha hydrogen atoms in the cyclic acetal structure is 8.7% of the integral of hydrogen atoms in the methoxy group.

[0061] 48 grams of the obtained moldable granules were evenly spread in a square mold of 100 mm×100 mm×25 mm, and then hot pressed at 180°C and 2 MPa for 10 min. After the hot pressing, cooling water was introduced, and the mold temperature was lowered to below 60°C. After the pressure was released, the mold was taken out to obtain the final molded product.

[0062] According to GB / T 17657-2013 "Test methods for physical and chemical properties of artificial boards and veneer artificial boards", the static bending strength and water resistance of the molded products were tested respectively. The results showed that its density was 0.78 g / cm 3 The static bending strength is 10 MPa and the thickness expansion rate of water absorption after 24 hours is 9%.

[0063] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A bio-based molding material, characterized in that: The main components of the molding material are uniformly mixed lignin and cellulose, the side chain of the phenol unit of the lignin contains a 1,3-dioxane cyclic acetal structure, the chemical shifts of the alpha carbon atom and hydrogen atom of the cyclic acetal structure in the two-dimensional nuclear magnetic resonance spectrum are äH: 4.5-5.5 ppm and äC: 92-105 ppm, respectively, and the integral of the alpha hydrogen atoms in the cyclic acetal structure should be greater than 2% of the integral of the hydrogen atoms in the methoxy group.

2. A bio-based molding material according to claim 1, characterized in that: Taking the total mass percentage as 100%, the mass percentage of cellulose in the bio-based molding material is 50-70%, the mass percentage of lignin is 30-50%, and the remainder includes hemicellulose and its derivatives.

3. The bio-based molding material according to claim 1, characterized in that: The particle size of the molding material is 10-100 meshes.

4. The bio-based molding material according to claim 1, characterized in that: The molding material is prepared by direct reaction of woody biomass containing lignin and cellulose as raw materials.

5. A bio-based molding material according to claim 4, characterized in that: Its preparation specifically comprises the following steps: 1) Mixing woody biomass with a first solvent, a second solvent, and a catalyst, heating to 70-140° C., and reacting for 20 min-8 h to obtain a mixed solution containing cellulose solids; 2) adding water to the mixed solution obtained in step 1) to precipitate lignin, thereby obtaining a mixed solution containing cellulose solids and lignin solids; 3) performing solid-liquid separation on the mixed solution obtained in step 2) to obtain a solid component and a solution component containing cellulose and lignin; 4) Drying the solid component obtained in step 3) to a moisture content of less than 5% to obtain a bio-based molding material.

6. The bio-based molding material according to claim 1, characterized in that: The molding material is obtained by pre-preparing lignin containing a cyclic acetal structure of 1,3-dioxane and then compounding the lignin with a cellulose-containing biomass material.

7. The bio-based molding material according to claim 6, characterized in that: The preparation method of the lignin containing the cyclic acetal structure of 1,3-dioxane is as follows: woody biomass is mixed with a first solvent, a second solvent and a catalyst, heated to 70-140° C., reacted for 20 min-8 h, to obtain a mixed solution containing cellulose solids, after removing the cellulose solids by solid-liquid separation, water is added to the obtained reaction solution to precipitate lignin solids.

8. A bio-based molding material according to claim 5 or 7, characterized in that: The first solvent is one or more of 1,4-dioxane, 1,3-dioxane, tetrahydrofuran, 2-methyltetrahydrofuran, γ-valerolactone, and acetic acid; the second solvent is an aqueous solution of one or more of formaldehyde, acetaldehyde, propionaldehyde, and butyraldehyde with a mass concentration of 35%-50%; and the catalyst is sulfuric acid or hydrochloric acid.

9. A bio-based molding material according to claim 5 or 7, characterized in that: The amount of the woody biomass used is 3-30% of the total mass of the first solvent and the second solvent; the amount of the first solvent used is 60%-99.4% of the total mass of the first solvent and the second solvent; the amount of the catalyst used is 0.1-5% of the total mass of the first solvent and the second solvent; and the amount of water added is 2-10 times the total volume of the first solvent and the second solvent used.

10. The bio-based molding material according to claim 1, characterized in that: The molding material can be directly molded, and the molding temperature is 160-250°C, the pressure is 2-40 Mpa, and the time is 10 s-60 min.